Quinone-catalyzed oxidative deformylation: synthesis of imines from amino alcohols - Liu, Xinyun; Phan, Johnny H.; Haugeberg, Benjamin J.; Londhe, Shrikant S.; Clift, Michael D. (Beilstein Journal of Organic Chemistry, 2017)
A new method for imine synthesis by way of quinone-catalyzed oxidative deformylation of 1,2-amino alcohols is reported. A wide range of readily accessible amino alcohols and primary amines can be reacted to provide N-protected imine products. The methodology presented provides a novel organocatalytic approach for imine synthesis and demonstrates the synthetic versatility of quinone-catalyzed oxidative C–C bond cleavage.
Keywords: catalysis; deformylation; organic synthesis; organocatalysis